1998
DOI: 10.1080/09712119.1998.9706214
|View full text |Cite
|
Sign up to set email alerts
|

Utilisation of Barley Straw by Steers: The Effect of Quantity and Source of Nitrogen on the Degradation of Straw Fractions, Particle Outflow Rate and Intake

Abstract: Nsahlai, I.V., Bryant, M.J. and Umunna, N.N. 1998. Utilisation of barley straw by steers : The effect of quantity and source of nitrogen on the degradation of straw fractions, particle outflow rate and intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Since the change in the rate of digestion of N-deficient roughage following supplementation with N is inversely related to the intrinsic quality of the roughage (Nsahlai 1991;Nsahlai et al, 1998a), it is likely that our use of the rate of digestion (k dig ) derived under dietary conditions that are different to those imposed during the in vivo digestion studies would negatively impact on the performance of the simulation model. Moreover, the current implementation of the nylon bag technique does hardly account for the selective feeding of stall fed animals, which could result in underestimation of the k dig of ingesta since it has been shown that sheep select a diet which is 2 -5% more degradable than the offered feed (Nsahlai et al, 1998b). The degree to which the above two opposing effects can counterbalance each other is yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Since the change in the rate of digestion of N-deficient roughage following supplementation with N is inversely related to the intrinsic quality of the roughage (Nsahlai 1991;Nsahlai et al, 1998a), it is likely that our use of the rate of digestion (k dig ) derived under dietary conditions that are different to those imposed during the in vivo digestion studies would negatively impact on the performance of the simulation model. Moreover, the current implementation of the nylon bag technique does hardly account for the selective feeding of stall fed animals, which could result in underestimation of the k dig of ingesta since it has been shown that sheep select a diet which is 2 -5% more degradable than the offered feed (Nsahlai et al, 1998b). The degree to which the above two opposing effects can counterbalance each other is yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…A passage rate (k) of 0.03 h À1 was assumed in order to calculate the effective degradabilities (ED) of DM and N. 25,26 The equation used was that proposed by McDonald: 22…”
Section: Calculations and Statistical Analysismentioning
confidence: 99%
“…A model developed by McDonald [ 11 ] was fitted on Statistical Analysis System 9.3 (SAS Institute Inc., Cary, NC, USA) and degradation parameters generated. Effective degradability (ED) was calculated using a passage rate of 0.03 per h [ 12 ]. The model used was: Y = a+b(1–e −c(t–L) ), where: Y, degradability at time (t); a, intercept; b, potentially degradable fraction; c, rate of degradation of b; and L, lag time.…”
Section: Methodsmentioning
confidence: 99%